Simulating Environmental Impacts Based On The Example Of Roşia Montană - Barton, Gábor (Journal of Environmental Geography, 2015)
One of the challenges of modern terrain modelling methods is to incorporate non-existing, planned features in the output. Remote sensing based solutions can only detect structures and shapes that are already present in the environment. In order to assess the impacts of a planned development on the surrounding landscape properly it is inevitable to solve this issue. In addition to the environmental, social and economic consequences, mining activities, especially open cast mining will also leave significant scars on the landscape. These can not only have a visual effect but also impact local weather conditions by changing winds, precipitation patterns. The current paper demonstrates a collection of methods and techniques able to cope with the various challenges that arise when modelling the landscape impacts of such developments. The experiments were performed in the area of Roşia Montană, where a Canadian company plans to create the largest open cast gold mine in Europe. The results of the terrain modelling process allow for the quantification of the estimated impacts on the terrain and the land cover of the area caused by the mining project. The presented methodology and visualisation tools can also facilitate the decision support mechanisms making the communication ‘more understandable’ amongst stakeholders; information meetings and public hearings involving organizing groups at any level. Obtaining the results required the development of several unconventional techniques especially in terrain modelling and visual landscape simulation, involving the combination of sometimes very different base methods.